Chez Fadette: Girlhood, Family, and Private Space inLate-Nineteenth-Century Saint-Hyacinthe - Adams, Annmarie; Gossage, Peter (Urban History Review / Revue d'histoire urbaine, 1998)
The histories of domestic space and domestic life have been written relatively independently in Canada. This article describes the preliminary results of an interdisciplinary project intended to narrow that gap. Based on both textual and non-textual evidence, the discussion turns on relationships between familial change and physical space in a bourgeois household in late-nineteenth-century urban Québec. The house is the childhood home of prominent journalist Henriette Dessaulles, known widely by the pseudonym Fadette. Ultimately, the authors make two distinct but inter-related arguments: First, that the built environment (the house) functions as a primary source in the larger study of family dynamics. And second, that important transitions in domestic life, such as remarriage, inspired women to take greater control of their own spaces.